Genetic basis of male sexual behavior. - Emmons, S.W.; Lipton, J. (Journal of Neurobiology, 2003)
Male sexual behavior is increasingly the focus of genetic study in a variety of animals. Genetic analysis in the soil roundworm Caenorhabditis elegans and the fruit fly Drosophila melanogaster has lead to identification of genes and circuits that govern behaviors ranging from motivation and mate-searching to courtship and copulation. Some worm and fly genes have counterparts with related functions in higher animals and many more such correspondences can be expected. Analysis of mutations in mammals can potentially lead to insights into such issues as monogamous versus promiscuous sexual behavior and sexual orientation. Genetic analysis of sexual behavior has implications for understanding how the nervous system generates and controls a complex behavior. It can also help us to gain an appreciation of how behavior is encoded by genes and their regulatory sequences.